ICU Emergencies Simulation Curriculum for Critical Care Fellows: Neurologic Emergencies - Jonathan M. Keller (Association of American Medical Colleges, 2019)
Introduction The management of neurologic emergencies is an important component of critical care fellowship training. Additional training in neurocritical care has been demonstrated to improve clinical outcomes, though exposure to these emergencies during training can be limited. Methods Three simulation cases are presented as part of a comprehensive neurologic emergencies curriculum for critical care trainees. The cases represent neurologic catastrophes encountered in the intensive care unit consisting of symptomatic hyponatremia, severe alcohol withdrawal syndrome, and brain herniation syndrome. The case descriptions are complete with learning objectives, critical actions checklists, and debriefing material for facilitators, as well as all necessary personnel briefs and required equipment. Results The scenarios were completed over the course of the 2016–2017 academic year by first-year critical care fellows. Following curriculum implementation, there was an improvement in self-perceived confidence of fellows in neurologic emergency management skills. Discussion The cases were felt to be realistic and beneficial and led to perceived improvement in management of neurologic emergencies and leadership during clinical crises.